Cyclic Voltammetric Studies of Arylisocyanidecobalt(I) Complexes with Tertiary Phosphine Ligands - A.L. BECKER, CLIFFORD; AHMAD, JAMIL (Asian Journal of Chemistry, 2010)
50 Arylisocyanide-Co(I) complexes with tertiary phosphine ligands, both monosubstituted [Co(CNR)4PR'3]X and disubstituted [Co(CNR)3(PR'3)2]X, X = ClO4, BF4, have been investigated by cyclic voltammetry in acetonitrile solution. Behaviour ranges from reversible to irreversible. Several distinct trends emerge. The Eox values systematically increase as substituents in the arylisocyanide ligand progress from electron- donating to electron-withdrawing. Sometimes this trend is reversed, possibly attributable to steric hindrance. The Eox values also systematically increase as the tertiary phosphine ligand becomes weaker σ-donating/stronger π*-accepting due to substituents. Trialkylphosphines show weaker π-acidity than triarylphosphines, except with electron-withdrawing substituents, like P(CH2Ph)3 and P(CH2CH2CN)3. Cobalt(I) complexes of 4:1 arylisocyanide: tertiary phosphine ligand composition tend to have substantially higher Eox values than 3:2 complexes with identical arylisocyanide and tertiary phosphine ligands.